An Exploratory Study of the Regional Context of Competitive Development in Romania - Valentin COJANU; Ileana PĂTRU-STUPARIU; Robert Răzvan DOBRE (Transylvanian Review of Administrative Sciences, 2011)
A recent series of EU initiatives have gradually changed the meaning of growth initiatives whereby the options of economic policy became more closely linked to the needs of development at ever smaller territorial units. The present research attempts to contribute to the discussion about the competitive potential of economic growth at territorial level. We introduce a methodological model to evaluate the conditions under which economic growth may generate opportunities leading to selfsustained economic development. The hypothesis is discussed at both national and regional scale and tested with a set of socio-economic variables including indicators relative to economic growth, economic functionality and spatial networks. Our findings suggest a huge potential in terms of capitalization of different types of capital (territorial, human, cultural), but also in terms of achieving mutual reinforcement of links between advanced and less advanced industries. Most of the national territory contributes insignificantly to the economic exploitation of resources through exports and advanced manufacturing. All this means resources which do not currently contribute to economic growth. Integrating the new concepts of territorial planning is gradual, long term oriented, and with significant learning economies. The objectives to pursue can be suggested from such measures as mapping of business operations in the target area or establishing non-governmental institutions with observation and monitoring roles.